Study on Water Quality of Sekadau River Using Pollution Index Method - Zulfian; Hardina, Ellan; Wahyuni, Dwiria (Jurnal Biologi Tropis, 2024)
One of the leading causes of declining water quality is contamination from human activities. The Sekadau River serves as a primary water source for the residents of Sekadau Regency, facilitating bathing, laundry, kitchen equipment cleaning, and freshwater fish cultivation. The objective of this study is to evaluate the water quality of the Sekadau River, comparing it against Class II standards as stipulated in Government Regulation No. 22 of 2021 on Environmental Protection and Management. Subsequently, pollution levels in the Sekadau River at the measurement point were determined using the Pollution Index Method (PIM). The research findings reveal that the pollution index values for 2018, 2022, and 2023 fall within the lightly polluted category. Conversely, in 2019, the water quality of the Sekadau River exhibited improvement. It complied with water quality standards per the Minister of Environment and Forestry Decree No. 115 on Quality Status Determination Guidelines. Consequently, the Sekadau River remains suitable for bathing, laundry, freshwater fish cultivation, and other purposes requiring water of the same quality as its designated use. However, considering the increasing pollution trends in 2022 and 2023, appropriate measures are necessary to prevent the Sekadau River from becoming more polluted.